প্রান্তজনের আপনজন ও নেপথ্যে নায়ক - বায়েস, আবদুল (BRAC University, 2016)
The Paper read out by Professor Abdul Bayes, Chair ESS in the workshop organized to celebrate Sir Abed's 80th Birthday at BRAC Centre Auditorium on 26 April 2016.